PENGARUH MEDIA APLIKASI MACROMEDIA DIRECTOR MX 2004 TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR - Kantari, Ade; Baysa, Muh. Husein (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
Abstract. The problem that occurs is the teaching and learning activities in the classroom centered on the media used by the teacher. The media used by teachers for presentations is to only used powerpoint applications that contain theories only, and teachers also sometimes used the lecture and question and answer method, when delivered material. So students do not understand the material presented by the teacher. The purpose of this study was to determine The Effect of Macromedia Director MX 2004 Application Media Towards Studentsâ€™ Outcomes Class X in Computer Subjects and Basic Networks at SMKN 1 Lingsar, West Lombok Regency in Academic Year 2019/2020.. Data collection techniques in this study used the test as the main method while documentation and observation as a complement. Data analysis techniques in this study used the ttest formula. The results obtained from the results of the t-test showed the t-test of 43.85, then based on a significant level of 5% and N = 37 it turned out that the amount of the rejection of the null hypothesis stated in the table was 2.042. This statement shows that the t-test value was greater than t-table (43.85> 2.042), because t-test was greater than t-table, this research was said to be significant. This means that the null hypothesis was rejected and the alternative hypothesis was accepted which reads: There was The Effect of Macromedia Director MX 2004 Application Media Towards Studentsâ€™ Outcomes Class X in Computer Subjects and Basic Networks at SMKN 1 Lingsar, West Lombok Regency in Academic Year 2019/2020., so it can be concluded that the results of this study are â€œsignificantâ€.